The physical, chemical and functional characterization of starches from Andean tubers: oca (Oxalis tuberosa Molina), olluco (Ullucus tuberosus Caldas) and mashua (Tropaeolum tuberosum Ruiz & Pavón) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The physical, chemical, and functional properties of starches isolated from the Andean tubers oca (Oxalis tuberosa M.), olluco (Ullucus tuberosus C.) and mashua (Tropaeolum tuberosum R. & P.) were studied. The tubers were obtained from a local grocery. The morphology of the starch granules (size and shape) was studied with scanning electron microscopy (SEM), which revealed ellipsoid, oval, conical, pear-shaped and prismatic forms: ellipsoids and oval granules with lengths up to 54.30 µm in oca; with lengths up to 32.09 µm for olluco starch granules; and with predominantly truncated spherical or oval forms and smaller dimensions (up to 16.29 um) for mashua starch granules. Amylose contents were similar among the samples: 27.60% (oca), 26.49% (olluco) and 27.44% (mashua). Olluco starch had less swelling power, forming opaque, less firm gels. All three starch gels showed the same stability on refrigeration and presented high syneresis under freezing temperatures, with a variation of 40.28 to 74.42% for olluco starch. The starches cooked easily, with high peak viscosity. The low gelatinization temperatures and high stability during cooling make these starches suitable feedstock for use in formulations that require milder processing temperatures and dispense freezing storage.